Environmental, social, and governance and hierarchical network data envelopment analysis firm efficiencies of Japan Airlines' supply chain - Kweh, Qian Long; Ting, Irene Wei Kiong; Asif, Jawad; Lu, Wen-Min (John Wiley and Sons Ltd, 2024)
Although environmental, social, and governance (ESG) have been recognized for its overall impact on firm efficiency, research on the effects of the three main and multiple sub elements of ESG, especially in the airline industry, has been lacking. Thus, we analyze the impacts of overall ESG, its three main elements, and each sub elements of ESG on the firm efficiency of 29 suppliers, partners, and customers of Japan Airlines over the period of 2013–2022. First, we employ a two-stage hierarchical network data envelopment analysis (DEA) technique that assesses the interrelationships and interdependencies among the supply chain players in contributing toward achieving their respective operating and profitability efficiencies. Second, we run ordinary least squares regression analyses with 5000 bootstrap replications and determine that overall ESG and its three main elements are positively linked with firm efficiencies. The sub elements of ESG have different impacts on firm efficiencies. That is, resource use and environmental innovation under the Environmental element and human rights and product responsibility under the Social element show significantly positive associations with firm efficiencies. All Governance sub elements positively affect firm efficiencies. The outcomes of this study will be valuable for managers at Japan Airlines and other policymakers within its supply chain because it highlights the importance of focusing on the three main and sub elements of ESG and employing the accurate firm efficiency measurement method when interrelationships and interdependencies of decision-making units exist.